(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article presents the results of a theoretical study on the basis of the parameters of a prikatka, which buries seeds of small-seeded vegetable crops planted in many rows to the same depth in a tapered way on the basis of agrotechnical requirements for the bushes prepared for planting and compacts the soil on the sides.